Building healthy life models centered on human and democratic values in a changing society - Ferreira, J. (Social work: Perceptions for a new era, 2024)
This chapter presents an essay based on social research, and professional and personal experience on the major issues facing contemporary society, ranging from quality of life, healthy living, the family, and the harmonization of social and human relations from a collective perspective. The structuring points I mention are human and democratic values from the humanist perspective of life in society; and some concerns about healthy models: opportunities, challenges, and uncertainties. We end with questions for reflection on a new balance in society's social life model. We are reinforcing the deepening of collective participation and the co-creation of societal models that promote greater social inclusion, quality of life, and social well-being.